Determinant of satisfaction towards e- commerce among youth customer in Malaysia - Bakri, Mohammed Hariri; Boo, Johnny Zhi Yang; Mello, Geraldine De (Human Resource Management Academic Research Society (HRMARS), 2024)
In this modern age, e-commerce had become a culture and a purchase behavior in our daily life. However, the customers will feel unsatisfied when the service provider can’t serve them appropriate. Thus, the current study was conducted to explain to determine the factor which will affect the youth customer satisfaction on E-Commerce Malaysia, the relationship between the youth customer satisfaction and E-Commerce Malaysia and the extent of the impact of the youth customer satisfaction toward E-Commerce Malaysia. Quantitative methods have been applied this research for data collection purpose. Data were collected on the five-point Likert scale through questionnaire survey from the youth residences Malaysia in Malacca. The data was gathered from 384 respondents located in Malacca, Malaysia. The reliability of the instrument was ensured by Cronbach’s Alpha test. In addition, Pearson Correlation and multiple regression tests had been applied to measure the nature and size of the association between variables and research hypotheses.